MOBILE-ASSISTED LANGUAGE LEARNING FOR DEVELOPING VOCABULARY MASTERY AMONG JUNIOR HIGH SCHOOL EFL STUDENTS IN INDONESIAN CONTEXTS - Syahrul Riza; Maidar Maidar (SENSEI RESEARCH CENTER, 2024)
Vocabulary is very important in English language learning. Many junior high school students have difficulty in remembering and using new words because vocabulary instruction is still dominated by word lists and translation. Nowadays almost all students have smartphones, so mobile devices can be used to help them learn vocabulary. This study discusses the use of mobile-assisted language learning for vocabulary development among junior high school students. The study used a mixed-method design with an experimental class and a control class. Data were collected through a vocabulary test, observation, interview, and journal. The result of the study shows that mobile-assisted language learning is better than conventional instruction and that the students gave a positive response to the activities. It is suggested that teachers use mobile applications in teaching vocabulary.